2009
DOI: 10.1111/j.1365-2702.2007.02150.x
|View full text |Cite
|
Sign up to set email alerts
|

Disease knowledge and treatment adherence among patients with thalassemia major and their mothers in Taiwan

Abstract: Improvement of the quality of patient care, reinforcement of medical education and enhanced efforts by clinical staff to provide practical knowledge to patients with thalassemia major should significantly improve patient adherence to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 22 publications
5
37
0
Order By: Relevance
“…The results confirmed such a hypothesis: 43% had inaccurate knowledge of the disease and treatment and only 48% adhered to the therapeutic regime (6) .…”
Section: The Impact Of Thalassemia Major and Its Treatments On The LIsupporting
confidence: 53%
See 1 more Smart Citation
“…The results confirmed such a hypothesis: 43% had inaccurate knowledge of the disease and treatment and only 48% adhered to the therapeutic regime (6) .…”
Section: The Impact Of Thalassemia Major and Its Treatments On The LIsupporting
confidence: 53%
“…The reports show that being an adult with thalassemia major is a difficult experience due to the frequency of return medical visits, periodic transfusions, the daily use of medication, side effects caused by the transfusions and medications, and social stigma, that alter daily life, as revealed in the literature (4)(5)(6)(7)(8) .…”
Section: Discussionmentioning
confidence: 99%
“…Disease knowledge was assessed by using 20 true or false questions measuring patients’ knowledge about TM from DKTM questionnaire …”
Section: Methodsmentioning
confidence: 99%
“…Other KAP studies in this group however had shown a link between knowledge score and practice. [34] It could be therefore concluded that improving the knowledge of TM patients and their families about the importance of calcium and Vitamin D in preventing osteoporosis could help improve their attitude and practice and thus lower the risk of osteoporosis-related complications and consequently reduce the burden of the disease in this group of patients.…”
Section: Discussionmentioning
confidence: 99%